Promoting geo-tourism at UNESCO global geo-park Belitong through geo-product development in small medium enterprise - Yuliawati, Ayu Krishna; Rofaida, Rofi; Gautama, Budhi Pamungkas; Hadian, Mohamad Sapari Dwi; Aryanti, Asti Nur (International Journal of Communication and Society, 2022)
The research aims to understand: how small and medium enterprises (SMEs) develop geo-product to promote geo-tourism and identify the supporting also inhibitory factors. The method used exploratory survey method, quantitative and qualitative method also where data is obtained through survey questionnaire, interview and FGD to SMEs and stakeholder. The research findings: geo-products are interpretations of attractions (geodiversity, culture-diversity and biodiversity) in geo-tourism activities, the supporting factor in geo-product development are loan procedure, leadership and marketing skills. The inhibitory factors are: employees’ lack of skill, limited market access, and financial reporting skill. The stakeholders played a role in supporting geo-product development, such as providing training program and implement geo-tourism events to showcase geo-product. Private companies support SMEs through by enhancing product quality and civil society organization has contribution in capacity building. The research contributes to the knowledge development on geo-product, and its role in promotion of geo-tourism activities in the UNESCO Global Geo-park Belitong.